The Social Factors Impact on Sustainable Business Growth Perception Within the ESG Concept - Michal Erben; Michal Kuděj; Jan Kubálek (Amfiteatru Economic)
The research aimed to identify key factors within the social (S) pillar of ESG and quantify their influence on the perception of a firm's long-term financial performance. The study covered the V4 countries, focusing on the views of business owners and managers, collected in February 2024, on the role of the social pillar in sustainable growth. LRM tested the statistical hypotheses. The results of the V4 countries revealed that a positive perception of company sustainability is primarily shaped by transparent ESG reporting, fair employee evaluation, work-life balance standards, respect for human rights, and strong community relations. Transparent reporting emerged as the most significant factor in determining positive attitudes toward sustainability. Although building good community relations and respecting human rights were less frequently cited, they still play an important role. Fair employee appraisal and work-life balance standards were also essential in shaping a company’s positive stance on sustainability